Development of Bodipy-Ir complex as an near-infrared photosensitizer for photoacoustic imaging-guided photodynamic therapy. (January 2023) - Liu, Chuangjun; Jiang, Yingchun; Xiang, Jingjing; Xiang, Chunbai; Li, Hongfeng; Li, Huacheng; Wei, Fangfang; Huang, Jiahao; Li, Rongqiang; Man-Chung Wong, Keith; Gong, Ping
Abstract: Herein we develop a novel NIR photosensitizer, bodipy-Ir. Under 808 nm excitation, bodipy-Ir could generate significant amount of singlet oxygen. In addition, bodipy-Ir exhibits photoacoustic properties as well. Thus, the photoacoustic imaging-guided photodynamic therapy of bodipy-Ir has been demonstrated. Graphical abstract: A Bodipy-derived NIR excitable photosensitizer for the PA imaging-guided photodynamic therapy. Image 1 Highlights: A Bodipy-derived NIR excitable ligand was developed. A NIR excitable photosensitizer based on Bodipy-Ir complex was constructed. The PA imaging-guided photodynamic therapy was demonstrated.